The effect of plant domestication on host control of the microbiota - Riccardo Soldan (Nature Portfolio, 2021)
Soldan and co-authors propose an evolutionary framework for understanding how host control of the microbiota is influenced by artificial selection. They go on to discuss the potential effect of domestication syndrome on the seed microbiome and plant-microbe interactions in the spermosphere.